2017
DOI: 10.3390/su9101795
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Low P-Emission Substrate for the Protection of Urban Water Bodies Collecting Green Roof Runoff

Abstract: Urbanization leads to higher phosphorus (P) concentration in urban catchments. Among different stormwater retention measures, green roofs are the least efficient in phosphorus retention. Moreover, much research has shown that green roofs act as sources of phosphorus, and they can emit P in significant loads. In this study low P emission green roof substrate was developed based on the proposed step by step procedure for the selection of materials including laboratory tests, column experiments, and the monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 52 publications
1
28
1
Order By: Relevance
“…Most green roof substrates are a mixtures of mineral and organic compounds. The most popular mineral components are: clay, sand, volcanic materials, crushed brick, and expanded lightweight materials, and among organic components, the most popular are: compost and peat [4]. Compost typically has very high P content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most green roof substrates are a mixtures of mineral and organic compounds. The most popular mineral components are: clay, sand, volcanic materials, crushed brick, and expanded lightweight materials, and among organic components, the most popular are: compost and peat [4]. Compost typically has very high P content.…”
Section: Introductionmentioning
confidence: 99%
“…Compost typically has very high P content. Buffam and Mitchell [5] obtained the value of leachable phosphate of above 200 mg•P-PO 4 3− /kg in deionized water extract. Toland et al [6] reported that SRP concentrations in runoff from green roofs with compost were more than 10 times greater than SRP concentrations without compost added.…”
Section: Introductionmentioning
confidence: 99%
“…Only one sample (SM1) of 13 tested substrates was within this limit ( Figure 5). SM1 is the mineral substrate developed as a "low P emission substrate" [32]. Mineral-organic substrates (SMO 1-7) were characterized by high P content (37.68-713.23 mg/kg), as well as second mineral substrate SM2 (554.16 mg/kg) and Sedum mates Ma1-4 (24.79-917.09 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the review given in [32], the most popular mineral components of green roof substrates are stated as clay, sand, volcanic materials, crushed brick, and expanded lightweight materials, while the most popular organic components are compost and peat. For the purpose of this study, tested mineral substrate compounds were characterized as natural origin (17 samples) and man-made (12 samples).…”
Section: Methodsmentioning
confidence: 99%
“…The benefits of green-roof contribute to some environmental aspects, including increasing biodiversity, reducing the effects of urban heat island [1][2][3][4][5], decreasing the thermal temperature of buildings [6][7][8]; on the economic aspect, including reducing maintenance costs and lowering operational costs [9][10][11]; and on aspects of social space, where people have access to green areas [12][13][14]. Economically, green-roof initiatives are feasible under certain conditions, but consideration needs to be paid to the construction costs of green-roof for the entire roofs of the buildings [9].…”
Section: Prospect Of Green Roofs Toward Sustainability Developmentmentioning
confidence: 99%